THE EFFECT OF JOB STRESS AND LOCUS OF CONTROL ON EMPLOYEE PERFORMANCE (Study on Employees of PT Bank Tabungan Negara Medan Branch Office) - Sitinjak, Rihot; Marpaung, Nicholas (Transpublika Publisher, 2025)
The aim of this study is to examine how work stress and locus of control impact the performance of employees at PT Bank Tabungan Negara (Persero) Medan Branch Office. This research utilises a quantitative approach with an associative methodology. The target population includes 158 employees at the Medan branch office of the state savings bank. Sampling was conducted using probability sampling techniques and the slovin formula, resulting in a total of 61 respondents. Data was collected through primary sources such as observation, interviews, and questionnaires, while secondary data was obtained through a review of existing literature. The analytical methods used are validity testing, reliability testing, classical assumption testing, multiple linear analysis, and hypothesis testing the results of the research conducted show that the variables of work stress and locus of control have a partial and significant effect on employee performance. The work stress variable and locus of control have a simultaneous and significant effect on employee performance. The resulting coefficient value shows that the relationship between the work stress variable and locus of control on employee performance is very strong with an r value of 0.885 or 88.5%. The adjusted r square value also shows that work stress and locus of control variables can explain employee performance variables by 77.6% while the remaining 22.4% is influenced by other variables not explained in this research.